Вплив конструкції корпуса букси на ресурс підшипників вагонів - Мартинов, Ігор Ернстович; Труфанова, Альона Володимирівна; Аулова, Надія Сергіївна (НТУ "ХПІ", 2017)
Багаторічний досвід експлуатації на залізницях України циліндричних буксових підшипників свідчить, що вони мають недостатню надійність. Фактична довговічність залізничних буксових підшипників суттєво менше за розрахункову. Однією з причин є нерівномірне розподілення навантаження як між тілами кочення, так і уздовж твірної роликів. Перспективним напрямком розв’язання цієї проблеми може бути забезпечення раціонального розподілення навантаження на підшипники буксового вузла шляхом створення змінної жорсткості корпусу букси в різних напрямках та надання можливості самовстановлення колісної пари під час руху вагона, особливо на кривих ділянках колії.

Long experience of exploitation of cylindrical axle bearings on Ukrainian railways shows that reliability of these bearings is low. Real durability of these bearings is muck lower than a calculated durability. One of the reasons is an uneven load distribution, both between rolling elements and along a generatrix. A promising way to solve this problem is to ensure a rational load distribution on the bearings by creating an axle box housing with a variable hardness in different directions and granting to a wheelset an ability of self-alignment during the movement of the wagon, especially on track transition curves. Improvement of safety the Railways in Ukraine can be achieved through the modernization less reliable elements of cars in order to eliminate failures in operation. In this article issues of improving axle boxes of wagon. Analysis of international experience of design and operation of the axle unit bearings suggests that one way to improve the reliabi lity roller bearings may be changing the body of the box. The article analyses scientific publications relevant to the forces acting on the bearing of rolling stock and focuses on the axle-box heating process. The purpose of the research is to determine reasons for a change in the heating temperatures variations and tendencies a depending of the of different axle-boxes of rolling stock.
Influence of a design of an axle box on the resource of bearings
Keywords: буксовий вузол; вантажний вагон; циліндричний підшипник; надійність; довговічність; корпус; axle unit; goods wagon; cylindrical axle; reliability; durability; housing